Call and Response - Jesse Foster Honsa (Footprint)
A "housing crisis" is often naively understood as a simple market imbalance between supply and demand, frequently occurring within cities in a capitalist mode of development. If that were the case, the solution would be to simply open the pipes and build more houses, a regulatory action delegated to technocrats. But as Reinhardt Koselleck reveals, crisis is a concept constructed by special interest groups with the aim of challenging absolute power, enlarging a sphere of popular criticism towards business-as-usual. This paper considers the operative nature of 'housing crisis' and related terms by investigating their use as a tool for urban reform in the 19th and 20th centuries in London. In newspaper articles, think tank publications and government reports, criticism often took on qualitative dimensions, leveraging change to housing practices. Crisis itself has had different meanings, from a moral apocalypse to a political risk to an historic opportunity. This is in contrast to how the term is used today, where it is no longer a climactic moment of decision and relief, but a perpetual and seemingly unsurmountable condition. While London's housing crisis is today universally accepted according to experts' statistics, it is rarely addressed on popular aesthetic grounds.